2021
DOI: 10.1007/s10677-021-10188-2
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Psychologism about Collective Intention

Abstract: This paper argues that a class of popular views of collective intention, which I call “quasi-psychologism”, faces a problem explaining common intuitions about collective action. Views in this class hold that collective intentions are realized in or constituted by individual, mental, participatory intentions. I argue that this metaphysical commitment entails persistence conditions that are in tension with a purported obligation to notify co-actors before leaving a collective action attested to by participants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…For instance, Chiu et al (2019) demonstrated common bond attachments and common identity as organisms that intervene between virtual community cues (stimuli) and virtual community citizenship behaviours (response). Similarly, collective intention reflects a socio‐psychological perspective as it is a combination of individuals' participatory intentions along with their perceptions of others' participatory intentions (Rachar, 2021). In coherence with previous research studies, the current research extends the understanding of the theory by adopting a socio‐psychological perspective on the organism concept.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…For instance, Chiu et al (2019) demonstrated common bond attachments and common identity as organisms that intervene between virtual community cues (stimuli) and virtual community citizenship behaviours (response). Similarly, collective intention reflects a socio‐psychological perspective as it is a combination of individuals' participatory intentions along with their perceptions of others' participatory intentions (Rachar, 2021). In coherence with previous research studies, the current research extends the understanding of the theory by adopting a socio‐psychological perspective on the organism concept.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…5 Many authors distinguish between ambiguous terms with more than one unrelated meaning and polysemy, which involves several associated or related meanings (cf., Löhr, 2021 for an overview). 6 Authors who have recently discussed such commitments and entitlements are Clark, 2006;Gilbert, 2013;Bratman, 2013;Tuomela, 2013, Roth, 2017Geurts, 2019;Alonso, 2016;Rachar, 2021. I build on these authors here but diverge from them substantially.…”
Section: Introductionmentioning
confidence: 97%